AVICENNA’S CONTRIBUTION TO WORLD MEDICINE - Djamaldinova Shahlo Obloberdievna; Bekirova Elzara Seydalievna (Galaxy International Interdisciplinary Research Journal, 2021)
The article describes the role of the works of Ibn Sino in the field of medicine and his great contribution to the treasury of human culture and the importance of Avicenna’s views in medicine.